PEMANFAATAN PANEL SURYA UNTUK SISTEM PENERANGAN KANDANG AYAM DI KEPANJEN, KABUPATEN MALANG - Ratna Ika Putri; Mila Fauziyah; Muhammad Rifa’i; Supriatna Adhisuwignjo; Yulianto Yulianto (Aptekmas Jurnal Pengabdian pada Masyarakat, 2021)
The partner in this community service program is the Dua Putra farm located in the village of Sengguruh, Kepanjen, Malang Regency. Apart from the cage for laying hens, this Dua Putra farm also has a hatchery cage with a capacity of 1000 chicks. Lighting in the chicken coop is important, especially at night because in addition to functioning as lighting, it also functions as a heater. Currently, the lighting in the chicken coop still uses the PLN electricity network, so that every month the owner has to pay electricity costs, which of course will increase production costs. The purpose of this activity is to provide understanding, knowledge and skills to farmers regarding the use of renewable energy, especially solar heat as a source of electrical energy used for lighting in partner chicken coops. The methods used in this program are appropriate technology innovation, training and coaching as well as monitoring and evaluation of activities. Technological innovation is carried out through the manufacture of a chicken coop lighting system using a microcontroller-based solar panel. The lighting of the chicken coop is supplied by solar heat which is converted into electrical energy by solar panels. The lighting will turn on automatically in the afternoon. Training and coaching are carried out through the socialization of the use of solar panels for lighting and the practice of using and maintaining solar systems using solar panels.